2019
DOI: 10.1007/s00414-019-02074-5
|View full text |Cite
|
Sign up to set email alerts
|

Pigs vs people: the use of pigs as analogues for humans in forensic entomology and taphonomy research

Abstract: Most studies of decomposition in forensic entomology and taphonomy have used non-human cadavers. Following the recommendation of using domestic pig cadavers as analogues for humans in forensic entomology in the 1980s, pigs became the most frequently used model cadavers in forensic sciences. They have shaped our understanding of how large vertebrate cadavers decompose in, for example, various environments, seasons and after various ante-or postmortem cadaver modifications. They have also been used to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 58 publications
0
102
0
6
Order By: Relevance
“…It is therefore necessary to estimate the time that has elapsed since the death of a wild boar (Sus scrofa) found in the field, i.e., the postmortem interval (PMI). For domestic pigs (Sus scrofa domesticus), comprehensive forensic research has been undertaken [1], but little is known about the decomposition process of wild boar, and no systematic guidelines for PMI estimation have so far been available.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore necessary to estimate the time that has elapsed since the death of a wild boar (Sus scrofa) found in the field, i.e., the postmortem interval (PMI). For domestic pigs (Sus scrofa domesticus), comprehensive forensic research has been undertaken [1], but little is known about the decomposition process of wild boar, and no systematic guidelines for PMI estimation have so far been available.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned illustrates the current difficulties associated with quantifiably accounting for sources of variance and error as previously emphasized by Henssge and Madea [4] and Matuszewski et al [5] suggest that it is not possible to recommend a universal analogue for human cadavers in decomposition studies yet. Moreover, they emphasize that abandoning non-human analogues is not currently viable due to the myriad of challenges and restrictions currently limiting use of donated human cadavers for experimental taphonomic research and stress the need for further research to address these shortcomings.…”
Section: Taphonomic Anatomical Validation Studies Between Pigs and Humentioning
confidence: 90%
“…The logic is that the results from such studies are more directly applicable to forensic cases than data derived from research on non-human models. This argument remains to be proven and there are several issues with it, most recently summarized by Matuszewski et al [5]. As a start, there are biographic disparities between the donor population for experimentation and the general population to which results are meant to be extrapolated, namely age, body mass and underlying medical conditions that may impact decomposition cycles.…”
Section: Human Versus Animal Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown differences between pig and decomposition rates in some areas [28], but so far, no differences have been seen between insect species collected from pig and human cadavers [3,29,30] and insect development is dependent on temperature rather than carcass type. A recent review has shown that using pig carcasses as human proxies is much more practical than using human cadavers as it makes controlling for confounding parameters much easier and increases the ability to replicate carcasses [31].…”
Section: Discussionmentioning
confidence: 99%